Klondiker hauling logs during winter with dogsled team to Dawson, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "A Klondyker hauling wood to Dawson Y.T." Klondike Gold Rush.